(2x-1)(2x+1)=2(x-3)^2+x(2x-3) . 4x^2-1=2(x^2-6x+9)+2x^2-3x . 4x^2-1=2x^2-12x+18+2x^2-3x . 15x=19 . x=1\frac{4}{15} .
1)
x ∈ (7;+∞) ∪ x ∈ (-∞;-5)
2)
- 16\\x^2<16\\|x|<4\\x<4,~~x\geq 0\\-x<4,~~x<0" class="latex-formula" id="TexFormula2" src="https://tex.z-dn.net/?f=-x%5E2%20%3E%20-%2016%5C%5Cx%5E2%3C16%5C%5C%7Cx%7C%3C4%5C%5Cx%3C4%2C~~x%5Cgeq%200%5C%5C-x%3C4%2C~~x%3C0" title="-x^2 > - 16\\x^2<16\\|x|<4\\x<4,~~x\geq 0\\-x<4,~~x<0">
x ∈ [0;4)
x ∈ (-4;4)
3)
-1\\x^2-2x+1>0\\(x-1)^2>0\\(x-1)^2=0\\x=1" class="latex-formula" id="TexFormula4" src="https://tex.z-dn.net/?f=x%5E2-2x%3E-1%5C%5Cx%5E2-2x%2B1%3E0%5C%5C%28x-1%29%5E2%3E0%5C%5C%28x-1%29%5E2%3D0%5C%5Cx%3D1" title="x^2-2x>-1\\x^2-2x+1>0\\(x-1)^2>0\\(x-1)^2=0\\x=1">
x ∈ R \ {1}
ответ: выражение истино, кроме случая
Поделитесь своими знаниями, ответьте на вопрос:
Решить уравнение (2x-1)*(2x+1)=2(x-3)(2)+x(2x-3) (2)-степень
(2x-1)(2x+1)=2(x-3)²+x(2x-3)
4x²+2x-2x-1=2(x²-6x+9)+2x²-3x
4x²-1=2x²-12x+18+2x²-3x
15x=19
x=19/15